A co-registration approach between terrestrial and UAV laser scanning point clouds based on ground and trees features - Nicola Puletti; Simone Innocenti; Matteo Guasti (Annals of Silvicultural Research)
Accurate co-registration of terrestrial and aerial point clouds can provide a high-resolution description of tree components across large forest areas. However, a semi-automatic approach for co-registering point clouds is still needed, given the challenges in geospatial data processing, particularly in complex topographical conditions. The main objective of this study is to present the application of a novel procedure for the co-registration of point clouds obtained from terrestrial and UAV surveys in Mediterranean forests. The proposed methodology proves to be promising and will constitute the basis for experimentation on a larger scale.